Reviewing the Association between the History of Parental Substance Abuse and the Rate of Child Abuse - Mahmoud Yaghoubi-Doust (Addiction and Health, 2013)
Background: Substance abuse is a social, and health problem in Middle Eastern countries such as Iran. One of its most devastating effects is domestic violence against children. This study examined the association between the history of parental substance abuse, and rate of child abuse in Ahvaz, Iran. Methods: This was a case-control study. The study population included all parents with high school children in Ahwaz within the academic year 2012-2013. The sample size was 384 people in two groups; with a history of substance abuse (case group) and no history of substance abuse (control group). Multi-stage cluster random sampling method was used through the Cochran formula. The data collection tools included a Childhood Trauma Questionnaire (CTQ) (Bernstein, 1995), a demographic questionnaire, Duncan Socioeconomic Index (DSI), and a researcher-made questionnaire for the history of substance abuse. For data analysis, statistical indicators such as percentage, mean, standard deviation, t-test, and correlation and regression analysis were used. Findings: Data analysis showed that there was a significant positive correlation among parents with a history of substance abuse and domestic violence toward children. Mean and standard deviation of the violence level in families with normal parents were 61.34 ± 16.88, and in families with a history of substance abuse were 98.99 ± 32.07. Therefore, the test results showed that there was a significant difference between normal families and families with history of substance abuse and violence toward children (P < 0.001, t = 8.60). Conclusion: Based on the findings, the history of domestic violence and parental substance abuse (physical and emotional abuse, emotional and physical neglect) had a significant positive correlation with their behavior toward their children. After matching the two groups we found that the most common types of violence against children by their parents were, respectively, emotional violence (r = 58%), physical neglect (r = 54%), emotional neglect (r = 46%), and then physical violence (r = 39%). Keywords: Child Abuse, Childhood trauma questionnaire (CTQ), History of substance abuse, Parents, Aspects of domestic violence, Children